2017
DOI: 10.1111/jgh.13697
|View full text |Cite
|
Sign up to set email alerts
|

The low‐FODMAP diet in the management of functional dyspepsia in East and Southeast Asia

Abstract: Functional dyspepsia (FD) is a common disorder in East and Southeast Asia where subjects experience post prandial fullness/bloating, early satiety, belching, epigastric pain, and/or burning. A subset of patients with FD experience triggers exclusively related to meals, defined as the post prandial distress syndrome in the Rome IV guidelines. There is significant overlap of symptoms and implicated pathogenic factors with another common functional gastrointestinal disorder, irritable bowel syndrome (IBS) and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 53 publications
0
19
0
3
Order By: Relevance
“…In humans, indirect evidence of the presence of cologastric reflex comes from few studies—a study including IBS patients that reported increased upper GI symptoms with high FODMAP diet 28 ; a pediatric study demonstrating reduction of dyspeptic symptoms with relief of constipation by laxatives 29 ; and a recent study reporting relief of dyspeptic symptoms in FD patients after Rifaximin induced change in colonic microbiota 30 . Secondly, decreased short chain fatty acids production in colon with LFD, could lead to decreased chemoreceptor stimulation and modulation of immune response 17 . Also, reduction in osmotic pressure and gas production might lead to decrease stimulation of upper GI neural system, which is in a state of hypersensitivity in FD patients 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, indirect evidence of the presence of cologastric reflex comes from few studies—a study including IBS patients that reported increased upper GI symptoms with high FODMAP diet 28 ; a pediatric study demonstrating reduction of dyspeptic symptoms with relief of constipation by laxatives 29 ; and a recent study reporting relief of dyspeptic symptoms in FD patients after Rifaximin induced change in colonic microbiota 30 . Secondly, decreased short chain fatty acids production in colon with LFD, could lead to decreased chemoreceptor stimulation and modulation of immune response 17 . Also, reduction in osmotic pressure and gas production might lead to decrease stimulation of upper GI neural system, which is in a state of hypersensitivity in FD patients 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Low FODMAP diet (LFD) has proven to be effective in IBS patients in numerous prospective trials including a recent one in our population 15,16 . Dietary restriction of FODMAPs has been shown to improve DGBI symptoms in three out of four patients, 14 and LFD has been proposed to be beneficial in FD 17 . We planned this prospective, randomized trial to assess the efficacy of LFD in improving symptoms and QoL in patients with FD, compared with TDA.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have noted that a low FODMAP diet can improve both diarrhea and constipation [4], although less data is available for the constipation predominant subtype. More recently, studies have suggested that FODMAPs may alter upper GI motility, affecting intra-gastric pressure [20] and may be useful in the management of functional dyspepsia [21]. Extra-intestinal symptoms have not been well studied with the low FODMAP diet, although fatigue has also been noted to improve [22].…”
Section: Sensitivities (Non-allergic)mentioning
confidence: 99%
“…FD patients commonly complain symptoms related to food ingestion, including gluten and FODMAPs [96], and dietary intervention can be used to treat these patients [97].…”
Section: Symptoms Of Dgbi In Patients With Ncgsmentioning
confidence: 99%